The Kulliyyah of Allied Health Science : pioneering quality health and well-being - Abdul Rahman, Suzanah (IIUM Press, 2019)
This book analyses the International Islamic University Malaysia described as the “Garden of Knowledge and Virtue” and its multi-dimensional features. The University provides excellent educational facilities for its students and is internationally recognised for providing high-quality learning environments. It contains chapters, contributed by the first five rectors themselves, on the contributions they made during the duration they occupied the office. It also contains a chapter by the current rector that focuses on the challenges the University is likely to face and alerts the University community to face these challenges and lead the way. The book also contains chapters contributed by the deputy rectors and directors of the University explaining achievements in various areas that make IIUM a leading international centre of educational excellence. Finally, the book contains chapters written by academic administrator heading the faculties and departments providing a brief overview of the historical development of the institution, its current set-up and the contributions it makes towards achieving the University's mission of Islamisation, Integration, Internationalisation and Comprehensive Excellence. Taken as a whole, the book provides readers with a deeper understanding of the core concerns of IIUM from its inception to its current position.